Effects of frequency on electrical fatigue behavior of ZnO-modified Pb(Mg1/3Nb2/3)0.65Ti0.35O3 ceramics - Promsawat, Methee; Promsawat, Napatporn; Wong, Jenny W.; Luo, Zhenhua; Pojprapai, Soodkhet; Jiansirisomboon, Sukanda (Elsevier, 2017)
This work aims to study the effects of frequency on the electrical fatigue behavior of ZnO-modified Pb(Mg1/3Nb2/3)0.65Ti0.35O3 (PMNT) ceramics. Changes in microstructures, ferroelectric and piezoelectric properties of the ceramics at bipolar electrical fatigue frequencies of 5, 10, 50 and 100 Hz were observed. The thickness of damaged surface of the ceramics decreased with increasing frequency. The degradation of properties of the ceramics fatigued at low frequency was greater than those fatigued at high frequency. The degradation by electrical fatigue at lower frequencies, 5 and 10 Hz, could be caused by the effects of both field screening and domain pinning, while at higher frequencies the fatigue was mainly a result of the field screening effect. The fatigue properties of ZnO-modified PMNT ceramics was compared to Pb-based and Pb-free ferroelectric ceramics. It was found that the fatigue endurance of ZnO-modified PMNT ceramic was greater than that of hard PZT ceramic but less than that of Pb-free ferroelectric ceramic.
Keywords: Fatigue; Ferroelectricity; Microstructure; Piezoelectricity